Infectious hematopoietic necrosis (review) - K. A. Balakhnina; V. P. Melnikov (Ветеринария сегодня)
Aquaculture in the Russian Federation is an integral part of the agricultural industry of the state economy. Countries with high rates of aquaculture growth (Norway, USA, China, Japan, Canada, etc.) and increasing efficiency of fish farming are the cradles of infectious diseases, which, in case of improper control, invade the territory of other countries and spread to new areas, bearing the risks for the domestic industry too. In recent years, infectious hematopoietic necrosis (IHN) has caused significant damage to fish farms. In 2020, Estonia suffered heavy losses; more than 65 tons of rainbow trout died and were destroyed during the IHN outbreak with a mortality rate of 71%. This was the first IHN case in this country. The aggravation of the epidemic situation at Estonian fish farms poses a threat to the northwestern regions of the Russian Federation, where aquaculture is practiced (the Leningrad Oblast and the Republic of Karelia). In 2022, IHN outbreaks were reported in France, Italy, Finland, Germany, Denmark and Macedonia. IHN-caused deaths were reported at the river trout farm in Georgia in 2023 for the first time. The domestic aquaculture depends on the import of eggs and seed material from Norway, Denmark, Finland and other countries, therefore a regular disease monitoring is urgently needed. The paper provides a brief description of the IHN causative agent, describes its epidemiology, pathogenesis, clinical signs, post-mortem lesions, diagnostic tests, infection control and prevention measures. We have reviewed 88 literature sources to summarize the information.